Hormonal and reproductive risk factors in patients with breast cancer - Kalinowski, Paweł; Bojakowska, Urszula Jolanta; Kowalska, Marta Estera (Journal of Education, Health and Sport, 2017)
Introduction Epidemiological studies confirmed that the estrogens plays an important role in the pathogenesis of breast cancer. Aim The aim of the study was to examine the prevalence of reproductive risk factors for breast cancer in the group of patients with the disease of breast cancer. Material and methods The study was conducted in the period from September 2015 until April 2016. The method of diagnostic survey. The research tool was the original questionnaire. In total, data were collected from 200 patients with breast cancer. Data were analyzed using descriptive statistics methods. Results In the analyzed group the average age of menarche was 13.8 years with a standard deviation of 1.5. The average age of menopause was 49.3 years with a standard deviation of 4.9 years. Almost half of the surveyed women have two children. The average age of first birth was 24.2 years with a standard deviation of 4.4 years. Most women did not use oral contraceptives and hormone replacement therapy. Conclusions Among the risk factors, the occurrence of which has been observed in the study group should hormonal factors such as early menstruation and late menopause, reproductive factors, as well as taking exogenous hormones.